2012
DOI: 10.1038/jid.2011.432
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 2 Is Upregulated in Normal and Keloid Scars

Abstract: REFERENCESCaltagarone J, Hamilton RL, Murdoch G et al (2010) Paxillin and hydrogen peroxide-inducibleclone 5 (Hic-5) expression and distribution in control and Alzheimer disease hippocampus. J Neuropathol Exp Neurol 69:356-71 Deakin NO, Turner CE (2008) Paxillin comes of age. J Cell Sci 121:2435-44 Fisher GJ, Varani J, Voorhees JJ (2008) Looking older: fibroblast collapse and therapeutic implications. Arch Dermatol 144: 666-72 Hagel M, George EL, Kim A et al (2002) The adaptor protein paxillin is essential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…The altered expression levels when compared to normal skin fibroblasts were also maintained by keloid fibroblasts over the culture lifetime. This again suggests sustained modulation of gene expression and implicates epigenetic change as being important in the maintenance of the keloid fibroblast phenotype …”
Section: Epigenetic Mechanisms In Keloid Scarringmentioning
confidence: 84%
“…The altered expression levels when compared to normal skin fibroblasts were also maintained by keloid fibroblasts over the culture lifetime. This again suggests sustained modulation of gene expression and implicates epigenetic change as being important in the maintenance of the keloid fibroblast phenotype …”
Section: Epigenetic Mechanisms In Keloid Scarringmentioning
confidence: 84%
“…More evidence enforces the postulation that HDAC inhibitors directly regulate transdifferentiation of fibroblasts to myofibroblasts. 72 During scar formation, the HDAC2 protein amount is dramatically increased 73 and renal fibrosis is also successfully controlled by HDAC inhibitors. 74 75 …”
Section: The Role Of Hdacs In Cardiovascular Diseasesmentioning
confidence: 99%
“…Although histone acetylation is now well established to regulate gene expression during skin development and homeostasis, there is less information regarding its role during wound healing in the skin. Previous studies found Hdac1/2 expression in human migrating wound epithelial tongue and also in normal and keloid scars . Moreover, another group investigated the differential effects of different classes of HDAC chemical inhibitors during wound healing …”
Section: Epigenetic Reprogramming During Injury‐induced Epidermis Regmentioning
confidence: 99%